ANALYSIS OF HIV SUBTYPES AND CLINICAL STAGING OF HIV DISEASE/AIDS IN EAST JAVA - Ismail, Yulia; Soetjipto, Soetjipto; Wasito, Eddy; Nasronudin, Nasronudin (Institute of Topical Disease, 2012)
Human Immunodeficiency Virus type 1 (HIV-1) known to cause Acquired Immune Deficiency Syndrome (AIDS) disease are divided into several subtypes (A, B, C, D, F, G, H, J, K) and Circulating Recombinant Form (CRF). Different characteristics of subtype of the virus and its interaction with the host can affect the severity of the disease. This study was to analyze HIV-1 subtypes circulatingin HIV/AIDS patients from the East Java region descriptively and to analyze its relationship with clinical stadiums of HIV/AIDS. Information from this research was expected to complement the data of mocular epidemiology of HIV in Indonesia. This study utilited blood plasma from patients who had been tested to be HIV positive who sected treatment to or were reffered to the Intermediate Care Unit of Infectious Disease (UPIPI) Dr. Soetomo Hospital Surabaya from various area representing the East Java regions. Plasma was separated from blood samples by centrifugation for use in the the molecular biology examination including RNA extraction, nested PCR using specific primer for HIV gp120 env gene region, DNA purifying, DNA sequencing, and homology and phylogenetic analysis. Based on the nucleotide sequence of the HIV gp120 env gene, it was found that the most dominant subtypes in East Java were in one group of Circulating Recombinant Form (CRF) that is CRF01_AE, CRF33_01B and CRF34_01B which was also found in Southeast Asia. In the phylogenetic tree, most of HIV samples (30 samples) are in the same branch with CRF01_AE, CRF33_01B and CRF34_01B, except for one sample (HIV40) which is in the same branch with subtype B. HIV subtypes are associated with clinical stadiums (disease severity) since samples from different stages of HIV disease have the same subtype.